HOW TO INCREASE PRODUCT INNOVATION AND COMPETITIVE ADVANTAGE OF MSMES IN BATAM CITY - Mulyaningrum, Mulyaningrum; Yuwono, Wisnu; Esfandiany, Shelby; Budiman, Johny (TRIKONOMIKA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a very important role in economic recovery and enhancing a country's competitiveness. Facing competition from domestic and international firms, this study examines the complex relationships among business strategy, entrepreneurial orientation, authentic leadership, and their collective contribution to competitive advantage through innovation. Using a quantitative approach with online and offline questionnaires, the study focuses on manufacturing companies in Batam, with a sample of 341. Data was analyzed using SPSS and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal positive effects of authentic leadership and business strategy on both innovation and competitive advantage. Notably, innovation emerges as a key mediator, underscoring its essential role in strengthening competitive advantage. These findings provide valuable insights into the dynamics of MSMEs in Batam and offer practical guidance for enhancing competitiveness through strategic leadership and innovation.